(untitled) (Journal of Population and Development, 2024)
The article attempts to explore the socio-political consciousness in Dalits for their rights, equality and liberation. Fundamentally, the article studies Sharad Poudel’s social novel “Tapan” (2073 BS) from the Marxist concept of class consciousness connecting with Dalit consciousness. For this purpose, the researcher collects and uses the various criticism and literature to explore how the Dalit literary texts portray the Dalit issues, problems, political and economic disparity, their protest and resolutions based on theoretical and critical analysis. The select novel’s plots, characters and the major themes also reflect the socio-political consciousness in Dalits. Moreover, the article explores that class consciousness develops within the characters and they stand together in the same mission and set goal for their liberation. And, the ideologies and political consciousness make them more responsible for their people and society. The novel as Dalit literature depicts multiple-layers of socio-economic, cultural and political problems of Dalits and their protests against it. The researcher employs the qualitative methods with descriptive and analytical approach.